2020
DOI: 10.7759/cureus.9811
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Trends During the Initial Peak of the COVID-19 Pandemic in the Midst of Lockdown: Experiences From a Rural Trauma Center

Abstract: Background As the early peak phase in the coronavirus outbreak has intensified, stay at home mandates were advised requiring individuals to remain home to prevent community transmission of the disease. Further mandates escalated isolated environments such as school closures, social distancing, travel restrictions, closure of public gathering spaces, and business closures. As citizens were forced to stay home during the pandemic, the crisis created unique trends in trauma referrals, which consisted of atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 9 publications
7
57
2
Order By: Relevance
“…A staggering 59% reduction in the total admissions for the lockdown period compared to the historical period was observed. Similar dramatic decreases in trauma cases, from 37.6 to 57.4%, have been reported worldwide (Leichtle et al 2020;Kamine et al 2020;Jacob et al 2020;Comelli et al 2020;Nuñez et al 2020;Christey et al 2020;Morris et al 2020;Rajput et al 2020;Rhodes et al 2020;Navsaria et al 2020). Aside from the lockdown and curfew orders, fear of contracting COVID-19 while seeking medical attention, for both traumatic and even non-traumatic injuries, has also been cited as a possible reason for the universal decrease in admissions (Navsaria et al 2020;Leichtle et al 2020;Rajput et al 2020).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A staggering 59% reduction in the total admissions for the lockdown period compared to the historical period was observed. Similar dramatic decreases in trauma cases, from 37.6 to 57.4%, have been reported worldwide (Leichtle et al 2020;Kamine et al 2020;Jacob et al 2020;Comelli et al 2020;Nuñez et al 2020;Christey et al 2020;Morris et al 2020;Rajput et al 2020;Rhodes et al 2020;Navsaria et al 2020). Aside from the lockdown and curfew orders, fear of contracting COVID-19 while seeking medical attention, for both traumatic and even non-traumatic injuries, has also been cited as a possible reason for the universal decrease in admissions (Navsaria et al 2020;Leichtle et al 2020;Rajput et al 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Despite stringent restrictions on social and public life, patients still experience trauma. Although the COVID-19 pandemic still an on-going issue, the few reports related to its effect on trauma suggest that there has been a considerable reduction in the number of admissions and, in some cases, a change in the mechanisms of injury for which the patients require medical assistance (Leichtle et al 2020;Kamine et al 2020;Jacob et al 2020;Comelli et al 2020;Nuñez et al 2020;Christey et al 2020;Morris et al 2020;Rajput et al 2020;Rhodes et al 2020;Navsaria et al 2020). The primary objective of this study was to determine the effect of the COVID-19 pandemic and the associated lockdown on trauma admissions, as well as their influence on patient's demographics, mechanisms of injury, injury severity, and outcomes to the Puerto Rico Trauma Hospital (PRTH).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the trend observed by Rhodes, Petersen, and Biswas in the setting of a rural trauma center who reported that ISS scores did not significantly change after the pandemic. 12 There was a significant increase in the mean length of stay after COVID-19 but no change in the median length of stay. This finding cannot be fully explained by the data set, but it is possible that some patients have higher rates of complications, either infectious or otherwise following the pandemic.…”
Section: Discussionmentioning
confidence: 83%
“…This is supported by the trend observed by Rhodes, Petersen, and Biswas in the setting of a rural trauma center who reported that ISS scores did not significantly change after the pandemic. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 48 Of the 7 studies reporting the injury severity score (ISS) of patients presenting during the pandemic, 5 reported a similar or slightly reduced presenting ISS during the pandemic, when compared with pre-pandemic years. 34 , 40 , 49 , 50 , 51 However, 2 centres in the United States (US) reported an increase in presenting ISS of 13.7–33%. 29 , 52 …”
Section: Resultsmentioning
confidence: 99%